IMMUNOPHATOGENESIS OF THE ORAL EPITHELIAL MUCOSAL DESTRUCTION DUE TO MONOMER METHYL METHACRYLATE EXPOSURE THROUGH HYPERSENSITIVITY REACTION: IMUNOPATOGENESIS KERUSAKAN JARINGAN MUKOSA MULUT AKIBAT PAPARAN MONOMER METIL METAKRILAT MELALUI REAKSI HIPERSENSITIVITAS - oral epithelial mucosa (Dentika: Dental Journal, 2009)
A basic material of polymethyl methacrylate (PMMA) acrylic resins is methyl methacrylate (MMA) monomer andwidely used in dental medicine. It is primarily used for removable orthodontic, partial and full denture appliances, andalso for dental fillings. The facts and results of the previous studies showed that MMA might act as irritant in certainconcentration, and also as immunogen or allergen. This study examined the immunopathogenesis of oral mucosal tissuedestruction in patients exposed to MMA, by detecting the concentrations of plasma IL-4, IFN-Î³, TNF-Î±, serum IgG andIgE specific to MMA that mediated irritation and allergic reactions. The general objective of this research was to examinethe immunopathogenesis of oral mucosal tissue destruction in patients exposed to MMA. The study used observasionalcase control study design. Laboratory tests for all samples were assessing plasma IL-4, IFN-Î³ and TNF-Î± using directsandwich ELISA technique. Serum IgG and IgE specific to MMA were assessed by indirect ELISA. It was concludedthat MMA is immunogenic in patients exposed to MMA that can induce IgG anti-MMA. Furthermore, this study alsoproved that immunopathogenesis of oral mucosal tissue destruction in patients exposed to MMA did occur throughirritation and type I hypersensitivity reaction mediated by IgE, but occurred through type IV hypersensitivity reactions.